2020
DOI: 10.17576/3l-2020-2603-11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Written Corrective Feedback on Malaysian ESL Secondary Students’ Writing Performance

Abstract: The teacher plays a crucial role in providing good written corrective feedback (WCF), especially in Malaysia's education system. Numerous studies were conducted on its effectiveness and students' perceptions, but most were meant for tertiary education. This mixed method study identified the types of WCF provided by teachers during their English as a Second Language (ESL) writing pedagogical practices in five Malaysian secondary schools, and analysed the perceptions of 482 students and 15 teachers towards the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 37 publications
(43 reference statements)
3
17
1
Order By: Relevance
“…More specifically, the students and teachers held different views from their colleagues. In a recent study, Ganapathy et al (2020a) examined the attitudes of instructors and learners regarding WCF usage in Malaysia. The perceptions mostly aligned in terms of the importance and effectiveness of WCF and diverged in terms of the amount of feedback.…”
Section: Students' Perceptions Of Wcfmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the students and teachers held different views from their colleagues. In a recent study, Ganapathy et al (2020a) examined the attitudes of instructors and learners regarding WCF usage in Malaysia. The perceptions mostly aligned in terms of the importance and effectiveness of WCF and diverged in terms of the amount of feedback.…”
Section: Students' Perceptions Of Wcfmentioning
confidence: 99%
“…2.5 Teachers' perceptions of WCF EFL/ESL teachers' preferences for delivering WCF have been the subject of a sizable amount of research, and the findings have revealed variations in how feedback is provided. Generally speaking, writing teachers agree on the value of their written comments as part of their teaching strategies for writing, leading students to better achievement of the syllabus objectives (Ganapathy et al, 2020a). Similarly, Lee et al (2017) argue that instructors believe that WCF can enhance learning writing and feel obliged to use it to justify the grades they assign.…”
Section: Approaches For Teacher Wcfmentioning
confidence: 99%
“…Along this line of statement, strategy, context of learners, instruction methodology, interaction types such as teacher-student and student-student are vital elements in AFL. Those aspects, through questioning, are of benefit to have diagnostic information, change, and adapt teachers' instruction regarding students' needs (Choi & Li, 2012;Ganapathy et al, 2020;Nassaji, 2016;Park, 2018;Sarandi, 2016;Sritrakarn, 2018).…”
Section: Afl and Questioningmentioning
confidence: 99%
“…Questioning and Assessment for Learning (AfL) are inseparably related. Following the pattern of IRF/E as claimed by (Ganapathy, Ai, Tan, & Phan, 2020;Laeli & Setiawan, 2019;Lee, Mak, & Burns, 2015;Nassaji, 2016), teacher questioning is widely acknowledged as crucial technique in classroom discourse and is used evaluate the specific learning goals (Black & Wiliam, 2009;Gattullo, 2000;Jiang, 2014;Milawati, 2017;Widiastuti & Saukah, 2017). Focusing on feedback activity, teachers utilize questions to make their students more active resulting from meaning negotiation process both through explicit and implicit.…”
Section: Introductionmentioning
confidence: 99%
“…(Vasu et al, 2016;Mahmood et al, 2020). Furthermore, most of the studies found only focused on students' perception instead of teacher's perception (Ganapathy et al, 2020;Vasu et al, 2016;Saeb, 2016;Sobhani & Tayebipour, 2015). Thus, this study aims to fill the gap by investigating Malaysian secondary ESL teachers' perception of oral feedback.…”
Section: Introductionmentioning
confidence: 96%